THE RELATIONSHIP BETWEEN PARENTING STYLES AND THE SOCIAL SKILLS OF PRESCHOOL CHILDREN AT RA AN-NUR, PESANGAN SIBLAH KRUENG DISTRICT, BIREUEN REGENCY - Rika Mursyida; Fitri Hijri Khana; Siska Desta Roza (PT. Radja Intercontinental Publishing, 2026)
Parenting patterns are everything that parents do to shape the behavior of their children, including all warnings and rules, teaching and planning, examples of affection as well as praise and punishment. Social skills are the ability of individuals to communicate effectively with others both verbally and non-verbally according to the situation and condition Which There is on moment That,Where skills is learned behavior. This study is a quantitative correlation study using a Cross Sectional design . to determine the relationship between parenting patterns and the social skills of preschool-aged children at RA-An-Nur, Peusangan Siblah Kreung District, Bireuen Regency. The number of respondents in this study was 64 people. This research was conducted at RA An-Nur Peusangan Siblah Krueng, Bireuen Regency. Data collection was carried out in July 2021. Variable measurement used univariate and bivariate analysis with the chi-square test . The results of this study indicate that out of 19 children with authoritarian parenting styles, 9 children (47.4%) have capable social skills. Of the 35 children with democratic parenting styles, 28 children (80.0%) have capable social skills. Of the 10 children with permissive parenting styles, 6 children (60.0%) have capable social skills with a ???? -value of 0.044.